Sintesis basa Schiff dari vanilin dan p-Anisidin dengan metode Green Chemistry : Metode penggerusan (Solvent Free) - Aminata, Farreliza Ayu (Maliki Interdisciplinary Journal, 2024)
Schiff base compounds are compounds resulting from condensation reactions between active carbonyl compounds from aldehydes and primary amines. Schiff base has many benefits in various fields because it has active compounds that have biological and pharmacological activities. This study aims to calculate the percentage, melting point test results and chemical properties, as well as knowing the results of the FTIR, 1HNMR, and GS-MS spectrophotometer characterization. The Schiff basic compound was synthesized from vanillin and p-anisidin (1:1) using the grinding method with a grinding time of 20 minutes. The constant mass yield obtained from the Schiff base synthesis product compound 2-methoxy-4-((4-methoxyphenilimino)-methyl)phenol was 1.0191 grams, with a yield of 99.08%. The characteristic results of the synthesis product have a physical form in the form of a solid powder, dark green in color, with a melting point of 120oC. Based on the solubility test, the synthesized product is obtained which is soluble in NaOH. The FTIR spectrum indicates absorption in the 1589 cm-1 wave region originating from the bond (C=N). In the GC-MS analysis, a retention time peak of 26.585 minutes was found with the molecular ion m/z 257. This finding is consistent with the molecular mass of the target compound, namely the Schiff base 2-methoxy-4-((4-methoxyphenilimino)-methyl)phenol. The results of the 1HNMR characterization of the synthesis product showed that there were 9 proton sites that matched the 1HNMR pattern of the basic Schiff compound 2-methoxy-4-((4-methoxyphenilimino)-methyl)phenol. The typical signal from the imine group (C=N) was observed at a chemical shift of 8.36 ppm.